Analyzing Performance of Islamic and Conventional Bank in Southeast Asia: The Firm Size View - Vanica Serly; Dovi Septiari; Ade Elsa Betavia (Universitas Pendidikan Ganesha, 2020)
This paper examines how the firm size of Islamic and Conventional bank different in performance of efficiency, stability and asset quality. The result of the study is aimed to see the extent of Islamic banks compete with conventional banks in the ASEAN context. The type of this research is a comparative study. The data is obtained from 31 conventional banks and 17 Islamic banks in Southeast Asia over the period of 2013-2017. Collected data are analyzed using DEA Analysis, Loan Loss Provision, Loan Loss Reserves and Z_Score. The findings showed that there were differences in efficiency and stability between conventional banks and Islamic banks based on firm size.